When art informs: challenging stereotypes in a multicultural educational setting in Botswana - Donlisha Moahi; Elmarie Costandius (University of Johannesburg, 2018)
As classrooms become increasingly multicultural, authentic teaching and learning is essential to avoid the creation of a negative image of the 'other'. Using a case study from a secondary school, an interpretive analysis was used to gain insight into how students made sense of their experiences and the significance of art as a platform to negotiate stigmas and stereotypes in class and school. The project generated space and context for students with different backgrounds to tell their stories and hear each other. Students revealed that language and dialects are also fundamental components of culture that should be supported by the education system. Art can be an especially effective catalyst for developing a critical awareness of issues of race, immigration, difference, and privilege. It is a platform for the negotiation and construction of meaning and could contribute towards removing the historic inequalities and injustices created by a stratified society. How to cite this article: MOAHI, Donlisha; CONSTANDIUS, Elmarie. When art informs: challenging stereotypes in a multicultural educational setting in Botswana. Scholarship of Teaching and Learning in the South. v. 2, n. 2, p. 18-36, Sept. 2018. Available at: http://sotl-south-journal.net/?journal=sotls&page=article&op=view&path%5B%5D=43&path%5B%5D=24 This work is licensed under the Creative Commons Attribution 4.0 International License. To view a copy of this license, visit http://creativecommons.org/licenses/by/4.0/